2016
DOI: 10.3389/fmicb.2016.00458
|View full text |Cite
|
Sign up to set email alerts
|

Coral-Associated Bacterial Diversity Is Conserved across Two Deep-Sea Anthothela Species

Abstract: Cold-water corals, similar to tropical corals, contain diverse and complex microbial assemblages. These bacteria provide essential biological functions within coral holobionts, facilitating increased nutrient utilization and production of antimicrobial compounds. To date, few cold-water octocoral species have been analyzed to explore the diversity and abundance of their microbial associates. For this study, 23 samples of the family Anthothelidae were collected from Norfolk (n = 12) and Baltimore Canyons (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 181 publications
(273 reference statements)
6
108
1
Order By: Relevance
“…In contrast to observations from thermal stress experiments in the coral Acropora muricata (Lee et al., ), where total Gammaproteobacteria decreased while Verrucomicrobiaceae and total Alphaproteobacteria increased, we observed a general decrease in the relative abundance of Alphaproteobacteria OTUs and an increase in total Gammaproteobacteria OTUs in A. digitifera . Members of Alphaproteobacteria , specifically order Rhodobacterales, are ubiquitous in coral reef ecosystems (Lawler et al., ) and comprise one of the dominant orders of bacteria in corals (Kemp et al., ) while order Rhizobiales are potentially Symbiodinium ‐associated taxa (Ainsworth et al., ). It has been shown that Alphaproteobacteria are typically associated with reefs that have higher coral cover while Gammaproteobacteria and Flavobacteriales are abundant in more degraded algae‐dominated reefs (Kelly et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to observations from thermal stress experiments in the coral Acropora muricata (Lee et al., ), where total Gammaproteobacteria decreased while Verrucomicrobiaceae and total Alphaproteobacteria increased, we observed a general decrease in the relative abundance of Alphaproteobacteria OTUs and an increase in total Gammaproteobacteria OTUs in A. digitifera . Members of Alphaproteobacteria , specifically order Rhodobacterales, are ubiquitous in coral reef ecosystems (Lawler et al., ) and comprise one of the dominant orders of bacteria in corals (Kemp et al., ) while order Rhizobiales are potentially Symbiodinium ‐associated taxa (Ainsworth et al., ). It has been shown that Alphaproteobacteria are typically associated with reefs that have higher coral cover while Gammaproteobacteria and Flavobacteriales are abundant in more degraded algae‐dominated reefs (Kelly et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut tissue of A. agassizii was dominated by Spirochaetia, mostly represented by the genus Spirochaeta which was prevalent in all of the samples and accounted for as much as 80% relative abundance of the class. Spirochaetes are motile freeliving, facultative/obligate anaerobes (Leschine et al, 2006), associated with numerous marine invertebrates, among others, corals (Lawler et al, 2016;Van De Water et al, 2016), sponges (Matcher et al, 2017;Kellogg, 2019), sea stars (Jackson et al, 2018), and at the body surface of the regular sea urchin species Tripneustes gratilla (<15% relative abundance) (Brink et al, 2019). Such a prevalence inside the gut of a sea urchin has never been described and suggests a specific interaction between Spirochaeta and the Abatus host.…”
Section: Spirochaeta and Desulfobacula: Keystones Of The Abatus Micromentioning
confidence: 99%
“…studies (e.g., Littman et al, 2009;Pantos et al, 2015;Roder et al, 2015) have suggested that geographic location and environmental settings can determine the holobiont microbiome, whereas others (e.g., Hentschel et al, 2002;Fraune and Bosch, 2007;Montalvo and Hill, 2011;Lawler et al, 2016) have shown that bacterial communities are species-specific associations conserved over time and space. Moreover, coevolution of bacteria and coral has been proposed (Thompson et al, 2015), as it was demonstrated for Endozoicomonas symbionts in corals with contrasting life-history traits and across global scales (Bayer et al, 2013;Neave et al, 2016Neave et al, , 2017.…”
Section: Exaiptasia H2 and Cc7 Strains Only Share A Small Common Micrmentioning
confidence: 99%